2021
DOI: 10.3390/biomedicines9101481
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Omics Approaches to Characterize Molecular Mechanisms of Rare Ovarian Cancers: Recent Advances and Future Perspectives

Abstract: Rare ovarian cancers are ovarian cancers with an annual incidence of less than 6 cases per 100,000 women. They generally have a poor prognosis due to being delayed diagnosis and treatment. Exploration of molecular mechanisms in these cancers has been challenging due to their rarity and research efforts being fragmented across the world. Omics approaches can provide detailed molecular snapshots of the underlying mechanisms of these cancers. Omics approaches, including genomics, transcriptomics, proteomics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…As a result, if the CSF analysis is the first negative, it is suggested that it be repeated. [14] One disadvantage is that, while CSF cells are very selective in recognizing cancer cells, they are also hypoallergic.…”
Section: Literature Review Detection Of Cancer Cell Enzymes In the Csfmentioning
confidence: 99%
“…As a result, if the CSF analysis is the first negative, it is suggested that it be repeated. [14] One disadvantage is that, while CSF cells are very selective in recognizing cancer cells, they are also hypoallergic.…”
Section: Literature Review Detection Of Cancer Cell Enzymes In the Csfmentioning
confidence: 99%
“…The biological activity of metabolites is a systems biology issue [53][54][55][56][57]. Combining metabolomics with other omics is attractive because the integration elucidates networks of molecular mechanisms in tumorigenesis [58][59][60], and can enhance personalized medicine [61][62][63][64][65][66][67]. For instance, using combined MS and HPLC can obtain information about individual differences in a patient's metabolome and proteome, something that is difficult to achieve by solely using next-generation sequencing (NGS).…”
Section: Integration Of Metabolomics To Other Omic Platformsmentioning
confidence: 99%
“…Several difficult problems in obstetrics and gynecology have been explored using the promising new field of scientific breakthrough “OMICS” technology. 1 These methods rely on only a small quantity of biological material by performing a single experiment with cutting-edge molecular biology tools. 2 Although proteome research has traditionally been used in biomedical engineering for 2 distinct but overlapping purposes—identifying novel treatment targets and studying biomarkers—these 2 lines of investigation now often intersect.…”
Section: Introductionmentioning
confidence: 99%